Variations of Indole Metabolites and NRPS-PKS Loci in Two Different Virulent Strains of Xenorhabdus hominickii - Mollah, Md. Mahi Imam; Roy, Miltan Chandra; Choi, Doo-Yeol; Hasan, Md. Ariful; Al Baki, Md. Abdullah; Yeom, Hyun-Suk; Kim, Yonggyun (Frontiers in Microbiology, 2020)
Xenorhabdus hominickii ANU1 is known to be an entomopathogenic bacterium symbiotic to nematode Steinernema monticolum. Another bacterial strain X. hominickii DY1 was isolated from a local population of S. monticolum. This bacterial strain X. hominickii DY1 was found to exhibit high insecticidal activities against lepidopteran and coleopteran species after hemocoelic injection. However, these two X. hominickii strains exhibited significant variations in insecticidal activities, with ANU1 strain being more potent than DY1 strain. To clarify their virulence difference, bacterial culture broths of these two strains were compared for secondary metabolite compositions. GC-MS analysis revealed that these two strains had different compositions, including pyrrolopyrazines, piperazines, cyclopeptides, and indoles. Some of these compounds exhibited inhibitory activities against phospholipase A2 to block eicosanoid biosynthesis and induce significant immunosuppression. They also exhibited significant insecticidal activities after oral feeding, with indole derivatives being the most potent. More kinds of indole derivatives were detected in the culture broth of ANU1 strain. To investigate variations in regulation of secondary metabolite production, expression level of leucine-responsive regulatory protein (Lrp), a global transcription factor, was compared. ANU1 strain exhibited significantly lower Lrp expression level than DY1 strain. To assess genetic variations associated with secondary metabolite synthesis, bacterial loci encoding non-ribosomal protein synthase and polyketide synthase (NRPS-PKS) were compared. Three NRPS and four PKS loci were predicted from the genome of X. hominickii. The two bacterial strains exhibited genetic variations (0.120.67%) in amino acid sequences of these NRPS-PKS. Most NRPS-PKS genes exhibited high expression peaks at stationary phase of bacterial growth. However, their expression levels were significantly different between the two strains. These results suggest that differential virulence of the two bacterial strains is caused by the difference in Lrp expression level, leading to difference in the production of indole compounds and other NRPS-PKS-associated secondary metabolites.